A novel PHKA2 mutation in a Chinese child with glycogen storage disease type IXa: a case report and literature review - Junling Fu; Tong Wang; Xinhua Xiao (BMC Medical Genetics, 2019)
Abstract Background PHKA2 gene mutations can cause liver phosphorylase kinase (PhK) deficiency, resulting in glycogen storage disease type IXa (GSD IXa). Elevated liver transaminase levels and liver enlargement are the most frequent phenotypes of GSD IXa. However, whether the phenotypes are applicable to Chinese patients remains unclear. Case report A boy aged 2 years and 8 months with a history of episodic fatigue and weakness since he was 2 years old was referred to our endocrinology clinic. Apart from symptomatic ketotic hypoglycemic episodes (palpitation, hand shaking, sweating, etc.), no abnormalities of liver transaminase levels or liver size were found. To identify the aetiology of his clinically diagnosed hypoglycaemia, the proband and his parents were screened for PHKA2 gene mutations by next-generation sequencing. A heterozygous mutation (c.2972C > G, p.G991A) in PHKA2 was found in the proband and his mother. Twenty-one Chinese cases with GSD IXa have been reported in the literature to date, and elevated liver transaminase levels (95%) and liver enlargement (91%) are the most frequent phenotypes of GSD IXa in Chinese patients. Hypoglycaemia may be one of the early onset symptoms in infants with GSD IXa. Conclusions This study enriches our knowledge of the PHKA2 gene mutation spectrum and provides further information about the phenotypic characteristics of Chinese GSD IXa patients.